Design and construction of a platform for peptide production in Escherichia coli using Green Fluorescent Protein (2019)
The peptides have a broad spectrum of application in the human health, however their obtaining is a challenge due to the absence of simple, effective and profitable methods to produce them on a large scale. They have been produced using recombinant DNA techniques, but the methods have been inefficient in preventing proteolytic degradation and toxicity in bacteria. In this project, Buforin II was produced using the Green Fluorescent Protein (GFP) as a production platform. For this purpose, the insertion of the peptide in four different loops of the protein was evaluated using E. coli as a heterologous expression system, it means that exogenous DNA was introduced into the bacteria, the protein was extracted and, then, purified. It was demonstrated that the peptide can be produced using GFP, despite the fact that bacterial growth rates decreased between 3 and 31 per cent with respect to protein without insertions. The most successful case was the insertion in Lysine 101 (Lys 101), where growth decreased only 6.5% without induction and 7.1% with induction, while fluorescence increased about 131% after 24 hours, allowing to obtain approximately 10.35 mg of protein. This new production method is more effective and profitable, which allow to produce any peptide properly flanked and better camouflage the toxicity of some peptides.